Adição de ácido linolênico e L-carnitina na maturação oocitária: efeitos sobre o metabolismo celular, potencial de desenvolvimento e criotolerância de embriões bovinos produzidos in vitro - Leão, Beatriz Caetano da Silva [UNESP] (2016)
In order to improve the results of cryopreservation of bovine in vitro produced (IVP) embryos, this study was conducted with the main objective to assess the impact of in vitro maturation medium (IVM) supplementation with linolenic acid (ALA), associated or not with L-carnitine (L-car), on oocyte maturation and quality, specially regarding to lipid metabolism and on development and cryoresistance of produced embryos. Therefore, in a first step (Experiments I and II) were performed dose-response experiments to determine the optimal concentrations of ALA (0, 10, 50 or 100 μM) and L-car (0, 1, 5 or 10 mM) to be added to IVM medium, supplemented with 10% fetal calf serum (FCS) or 0.6% bovine sérum albumin (BSA). The effects of ALA and L-car on nuclear and cytoplasmic maturation [mitochondrial evaluation, intracellular lipid accumulation and intracellular production of reactive oxygen species (ROS)] and subsequent embryonic development were evaluated. In Experiment I, the IVM supplementation with 100 mM of ALA in FCS-supplemented medium resulted in reduction (P<0.05) of cytoplasmic lipid and intracellular ROS accumulation, as well as, increased (P<0.05) mitochondrial membrane potential (MMP), relative to the other ALA concentrations. However, none of these effects damaged (P<0.05) oocyte maturation and the subsequent embryo development potential. In Experiment II, the IVM medium supplementation with L-car resulted in significant reduction (P<0.05) of cytoplasmic lipid content even in the FCS presence. Combined effects of 10 mM L-car in FCS-supplemented medium on MMP reduction (P<0.05), ROS production increase (P<0.05), and the negative effect (P<0.05) on embryonic development of BSA IVM medium supplementation, we can conclude that concentration of 5 mM L-car in the presence of FCS exceeded the results of the other groups. Based on previous experiments results, in a second step (Experiment III), the effects of supplementation with ALA (100 μM), L-car (5 mM) or a combination of both treatments (ALA + L-car) during IVM culture, with 10% FCS were evaluated on subsequent embryo development and quality (assessed by total cell number and apoptosis rate), intracellular lipid and ROS content, in addition to embryonic cryotolerance. For this, oocytes were fertilized for 24 h and the presumptive zygotes in vitro cultured (IVC). Cleavage rate (48 hpi) and embryonic development until blastocyst stage (D7 IVC) were evaluated. Blastocysts were vitrified and subsequently warmed for post-cryopreservation embryo survival evaluation, after 24 h, and hatching rate, after 48 h IVC. The gene expression regulation of lipid metabolism related genes (lipogenesis regulation: SCD1, FASN and SREBP1; β-oxidation pathway regulation: CPT1B and CPT2), was also performed in this step. There were evaluated ALA and/or L-car supplemented oocytes during IVM culture, and the produced embryos. The treatments made in IVM step did not support the positive effects observed in the previous studies on the lipid content reduction and the improvement in oocyte development potential. They did not change the lipid content and therefore, embryonic cryotolerance. Despite this, there was an improvement in embryo quality by reduction of the apoptotic index and ROS production. Lipogenesis-related genes expression was influenced by the treatment conducted during IVM. However, for lipolysis-related genes, a potential positive effect was losted and, may be need the treatment on IVC step. Therefore, further studies are necessary to assess the most appropriate IVP step to perform ALA, L-car and the combination of both treatments supplementation, aiming changes in lipid content, and consequently the embryonic cryotolerance.